Characterization of 13 polymorphic microsatellite loci for the dogtooth tuna Gymnosarda unicolor - Bentley, B.; Harvey, Euan; Newman, Stephen; Welch, D.; Smith, A.; Kennington, W. (Springer, 2013)
We describe the isolation and development of 13 polymorphic microsatellite loci for the reef-associated dogtooth tuna Gymnosarda unicolor (Perciformes: Scombridae). The loci were tested on 20 individuals from a single population at Flinders Reef, located off the east coast of Australia. No evidence of linkage disequilibrium was detected between any pairs of loci. However, one locus showed a significant departure from Hardy–Weinberg equilibrium. The number of alleles per locus ranged from 2 to 12.